Impact of the Textual Discourse Model in writing essays in high school students - Núñez, Javier (2019)
The objective of this work was to determine the impact of the Discursive Textual Model in the writing of essays by fifth grade students of the I.E.S. María Auxiliadora of the city of Puno. A control group (section "G") and another experimental group (section "D") have been taken into account. In the experimental group, the Textual Discursive Model was applied through nine sessions. Each session consisted of two hours of theory and two hours of workshop. In order to achieve the objective of the research, the technique of Difference in Differences has been used. It has been concluded that the application of the Discursive Textual Model has a positive impact on the writing of essays. The students who participated in the workshops of the application of the Discursive Textual Model improved the production of essays by an average of 5 points as opposed to the students in the control group.